下顎埋伏智歯における舌側皮質骨のエックス線CT 画像所見とパノラマエックス線写真との対応に関する検討 - 中道, 由香; 大橋, 瑞己; 増田, 千恵子; 岡田, とし江; 住本, 和歌子; 中島, 博 (日本口腔外科学会雑誌, 2009)
To prevent the mandibular third molar from dropping into the pterygomandibular space after extraction of this tooth, it is important to understand the local anatomy. We studied the lingual cortical bone in patients with impacted mandibular third molars on CT scans and classified the bone into three groups: GroupⅠ, cortical bone defect; GroupⅡ, cortical bone thinning; and Group Ⅲ, normal cortical bone. Among 134 impacted mandibular third molars studied, 15（11.2 ％）, 36（26.9 ％）, and 83（61.9 ％）were classified into GroupsⅠ, Ⅱ, andⅢ, respectively. In GroupsⅠ andⅡ（38.1 ％）, the risk of the mandibular third molar dropping into the pterygomandibular space was considered high. The relation between the state of the lingual cortical bone and the depth of the impacted molar was examined on 114 panoramic radiographs. According to Winter’s classification of molar depth, the numbers of molars in A, B, and C position were 15, 23, and 10, respectively, among the 48 impacted mandibular third molars in GroupsⅠ andⅡ. There was no correlation between the state of the lingual cortical bone and molar depth. In conclusion, CT is useful for preventing the mandibular third molar from dropping into the pterygomandibular space during extraction of impacted mandibular molars.